The future of comparative effectiveness and relative efficacy of drugs: an international perspective. (August 2015) - Messner, Donna A; Towse, Adrian; Mohr, Penny; Garau, Martina
Drug development takes place in a global marketplace, albeit with the USA and EU markets currently dominating. In the USA, demands for comparative effectiveness research have gained traction against a backdrop of health delivery reform, while European stakeholders deliberate the role of relative effectiveness in health technology assessment, trying to reduce the duplication of effort by regulators and health technology assessment bodies. In both arenas, drug-makers are faced with mounting drug development costs, and uncertainty over the types of evidence acceptable for a growing list of stakeholders. This article reports and compares future scenarios for evidence expectations for drugs for the USA and EU in 2020. The similarities, differences, and joint implications of the scenarios are considered to create an view of future evidence generation for drugs developed for these markets.